OTHERWORLDLINESS IN THE CYCLE OF SHORT STORIES "GIRLFRIENDS" BY LYUDMILA ULITSKAYA (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article examines the cycle of short stories "Girlfriends" as part of Lyudmila Ulitskaya's[1] final book of short stories "About the body of the Soul".  The analysis uses the techniques of a structural-semiotic approach, as well as elements of motivic, intertextual and mythopoeic analysis. The author comes to the conclusion that in the stories of the cycle "Girlfriends" the category of otherworldliness is realized in many ways. Focusing on boundary spaces and states, the author approaches the idea of the fictitiousness of the real world. As a "guess" of this, the author models the other world, recreating possible options for transition / non-transition into otherness. The stories focus on the permeability of the boundary between the otherworldly and this world, and the possibility of communication between them. The cycle "Girlfriends" largely continues the themes that were found in the author's previous works. However, the metaphysical significance of the plots is brought to the fore. The cycle emphasizes the principle of binary: these are two worlds – life and death, soul and body, this is an ambivalent function of material details, oneiric spaces, this is the "pairing" of characters (Zarifa and Musya; Alice and Alexander; Salih and Lilya; Lida and Nina). At the same time, the coexistence of these two principles is built not only on a simple mirror image, but also on complex "labyrinthine" connections, which continue to be clarified in the second part of the collection "On the Body of the Soul." [1] Ulitskaya Lyudmila Evgenievna was included on March 1, 2024 by the Ministry of Justice of the Russian Federation in the register of media and individuals performing the functions of a foreign agent (No. 770).